Role of Panchakarma in Non- Communicable Diseases: Life Sciences-Ayurveda - Singh, Varinder; Parwe, Shweta; Sawarkar, Punam; Shrivastav, Poooja; Nisargandha, Milind (International Journal of Life Science and Pharma Research, 2023)
The global burden of non-communicable diseases is increasing rapidly, and adopting a healthy lifestyle is an important strategy to combat it. Ayurveda can play an essential role in this regard, as the main aim of Ayurveda is to prevent diseases by following a healthy lifestyle. However, to implement such traditional knowledge (that is based on a healthy lifestyle). Principles of Ayurveda) in actual practice, a systematic process should be followed. Ayurveda is a traditional system of medicine that applies holistic principles that primarily focus on personal health. Ayurveda originated in India and is one of the oldest healthcare traditions. Ayurveda is often known as the "science of life" because "Ayu" in Sanskrit means life, and "Veda" means science or knowledge. Vagbhatt’s Ashtanga Haridyama, Charaka Samhita, Sushruta Samhita (400 BC - 200 AD) and Ashtanga Hrudayam contain detailed descriptions of over 700 herbs and 6,000 sutras. This systematic process must involve serious research (i.e., development and evaluation). Ayurvedic-based lifestyle interventions) and behavioural change. This article explains the importance of Panchakarma therapies or procedures mentioned in Ayurvedic classical textbooks and their implementations to counter Non- Communicable Diseases. As a result, there is a greater goal to accomplish. Traditional knowledge of Ayurveda is found in actual practice that is useful for society. The aim is to explore and seek solutions or treatment options available in Ayurvedic classical texts for Non-Communicable diseases. The source for this study is collected from classical Ayurvedic books and commentaries, modern medical science textbooks and different articles from Pubmed, DHARA, GoogleScholar etc. Exploration of various Panchakarma procedures or therapies described in Ayurvedic classical texts helps us better understand pathologies of Non- Communicable diseases from their root causes and allow us to understand how potent Panchakarma therapies have a healthy influence to counter Non- Communicable diseases.